Pengembangan bahan ajar berbasis komik digital untuk menanamkan literasi ekonomi di sekolah dasar - Anisa Fitriani; Srie Mulyani; Jennyta Caturiasari (IKIP Siliwangi, 2024)
PENGEMBANGAN BAHAN AJAR BERBASIS KOMIK DIGITAL UNTUK MENANAMKAN LITERASI EKONOMI DI SEKOLAH DASAR Anisa Fitriani1, Srie Mulyani2, Jennyta Caturiasari3 1 UPI, Purwakarta, Indonesia2 UPI, Purwakarta, Indonesia3 UPI, Purwakarta, Indonesia 1 annisafitriani1230@upi.edu , 2 sriemulyani@upi.edu , 3 jennytacs@upi.edu AbstractThis research is motivated by three formulations of the problem, namely: (1) How to manufacture or design digital comic-based teaching materials (2) What is the feasibility test on digital comic-based teaching materials to instill economic literacy (3) What is the response of teachers and students to material digital comic-based teaching. The research method used is design and development (D&D) with the research procedure, namely the ADDIE model, which consists of five stages (Analysis, Design, Development, Implementation, Evaluation). The research location was carried out at SD EL FITRA. The research participants consisted of material expert validators, media validators, teachers and seven grade IV SD EL FITRA students. The results of the feasibility test from the material expert validator and media experts showed the category